Promising Role of Fruitless Wolfberry Bud Tea in Combating Nakaseomyces glabratus Resistance - Liping Zhang; Zhiyan Ma; Xuezhang Zhou; Ziping Zhang; Tao Wu (Pathogens)
The rising antifungal resistance in Nakaseomyces glabratus, especially to azole drugs like fluconazole, itraconazole, and voriconazole, presents a significant clinical challenge. Plant-derived compounds with synergistic antifungal effects offer a promising solution. Fruitless wolfberry bud tea, rich in flavonoids from a Lycium barbarum L. hybrid, shows potential but is underexplored in antifungal therapies. This study assessed FWE’s antifungal efficacy alone and with azoles against resistant N. glabratus isolates, exploring mechanisms like efflux pump inhibition and gene expression changes. A total of 52 clinical isolates were tested. Fruitless wolfberry bud tea was methanol-extracted (FWE) and lyophilized. Antifungal susceptibility was evaluated using broth microdilution, and synergistic effects were analyzed with checkerboard assays. Growth inhibition, rhodamine 6G efflux, and qRT-PCR for resistance-related genes were conducted. FWE demonstrated inhibitory activity with MICs ranging from 16 to 32 μg/mL. When combined with ITR or VRC, synergistic or additive effects were observed, reducing MICs by 2–8-fold. FWE + VRC exhibited synergy (FICI ≤ 0.5) in 50% of isolates, while FWE + ITR showed synergy in 37.5%. Efflux pump activity, measured by rhodamine 6G, significantly decreased in combination groups (11.4–14.6%) compared to monotherapy (17.3–17.5%). qRT-PCR indicated downregulation of CgCDR1, CgERG11, and CgPDR1 in FWE-treated Cg 1 isolate, with greater suppression in combination groups. FWE might boost the bacteriostatic impact of azole antifungal drugs by blocking efflux pumps and altering the expression of resistance genes. This study identifies FWE as a potent adjuvant to overcome cross-resistance, supporting its inclusion in antifungal strategies. Further research to identify bioactive compounds in FWE and in vivo validation is necessary for clinical application.